Forensic Stylistic Analysis in A Pragmatic Approach to an Indian Teenage Girl's Suicide Note - Karina Dea Amalia; Amelia Amanda Putri; Zarah Khodijah Yasmin; Hanny Shah Rahma Reswara Lubis; Rahmadsyah Rangkuti (Humanitatis : Journal of Language and Literature, 2024)
The background of this research stems from the need for an in-depth understanding of suicide notes, where language is used as evidence in a legal context. Utilization of a forensic stylistics analysis technique is crucial in the assessment of written texts in criminal investigations, with the objective of revealing indications of deception, narrative coherence, and implicit connotations within the text. This research aims to uncover the hidden meanings contained in the language used in suicide note writing. This study employed a descriptive qualitative research methodology to examine suicide notes obtained from the IndiaToday news website using a Google search. The method of data collection entails obtaining, reading, comprehending, and analyzing the suicide notes as major sources of evidence. The results of this study indicated the importance of understanding suicide communication from a pragmatic point of view and that social and psychological elements should be considered in dealing with suffering. With this research, it can be proven that language as evidence can have a major influence on the investigation process; it can show the audience that the words are not just words but words that have the meaning implied in the word.